PENERAPAN MODEL PEMBELAJARAN TGT (TEAM GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Nisa Humayroh; Hunaepi Hunaepi; Ida Royani; Yusria Hadiana; Baiq Deana Rahayuan (Universitas Singaperbangsa Karawang, 2019)
The purpose of this study is to improve the cognitive learning outcomes of Grade VII students of MTs Mambaul Abror 2018/2019 Academic Year through the application of the TGT (Team Games Tournament) learning model. This research is a Classroom Action Research (CAR), where the research subjects are Grade VII students of MTs Mambaul Abror in 2018/2019 with the object of research being the students' cognitive learning outcomes. Student cognitive learning outcomes data obtained through test questions are provided at the end of the learning cycle. The results obtained by the percentage of the implementation of the RPP in the first cycle of 56.3% with an unfavorable category the second meeting of 68.75% with a fairly good category. The percentage of RPP implementation in the second cycle was 81.3% in the good category while the second meeting was 93.8% in the very good category. For observations of student activities in the first cycle obtained a percentage of 50% with a fairly good category and the second meeting obtained a percentage of 64, 28% with a good category. The percentage of observations of student activities in the second cycle obtained the results of the first meeting of 78.6% with a very good category and the second meeting obtained a percentage of 100% with a very good category. While the cognitive learning outcomes of students obtained a percent of tage classical completeness in the first cycle by 55% and in the second cycle by 80%. So it can be concluded that the application of the TGT learning model (Team Games Tournament) can improve cognitive learning outcomes of Grade VII students of MTs Mambaul Abror 2018/2019 Academic Year.